Trace element dispersion in wallrocks of copper-bearing bodies, Namaqualand - Venter, J. P.(Jacobus Petrus) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1970.